2017
DOI: 10.1590/1413-785220172506166548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Treatment of Patients With Shoulder Instability

Abstract: Objective:To evaluate the results of arthroscopic surgery in patients with traumatic anterior shoulder dislocation. Methods:This retrospective study analyzed 76 patients with a mean age of 28 and mean postoperative follow-up period of 62 months. Evaluation consisted of physical examination, and X-rays; results were classified according to the UCLA and Rowe scales. Results:Patients showed decrease of range of motion in all planes, except elevation and lateral rotation with 90º abduction. According to the Rowe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…Acute anterior shoulder dislocation following trauma is a frequent injury that affects between 0.5 and 1.7% of people. Recurrence is reported in close to 90% of instances when it develops in young adults (13).…”
Section: Discussionmentioning
confidence: 99%
“…Acute anterior shoulder dislocation following trauma is a frequent injury that affects between 0.5 and 1.7% of people. Recurrence is reported in close to 90% of instances when it develops in young adults (13).…”
Section: Discussionmentioning
confidence: 99%
“…Martel et al[ 20 ] reported the development of glenohumeral osteoarthritis in four of 41 patients following a mean 33 (range, 12 to 47) month follow-up period after arthroscopic Bankart repair performed with metal suture anchors. Ikemoto et al[ 21 ] reported osteoarthritis development at the rate of 4% with bioabsorbable suture anchors and 21.5% with metal suture anchors after a follow-up period of mean 62 (range, 24 to 106) months after arthroscopic Bankart repair. No osteoarthritis development was observed in any patient in either of the two groups in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Com o surgimento de novos modelos de âncoras sem nó, evoluindo para serem absorvíveis e se fixarem ao osso por impacção de ranhuras laterais e não mais por aletas, alguns autores publicaram resultados comparáveis 16,50 aos de âncoras com nó também absorvíveis 10,51 . Até o momento foram publicados dois trabalhos, um prospectivo com randomização por ordem de entrada dos pacientes no estudo 47 em 2014 e um retrospectivo 48 em 2020, comparativos entre o uso de âncoras absorvíveis com nó e sem nó de última geração.…”
Section: Algunsunclassified
“…Ikemoto et al 10 em 2017 publicam estudo retrospectivo de série de casos de 76 pacientes operados com âncoras absorvíveis com nó com seguimento médio de 62 meses. Apresentam perda de amplitude de movimento em todos os planos exceto elevação e rotação lateral em abdução de 90 graus.…”
Section: Objetivosunclassified
See 1 more Smart Citation